Vertaling en/as abjeksie: Antjie Krog - Vosloo, Franci (Stellenbosch Papers in Linguistics Plus, 2014)
OpsommingInternasionaal bekroonde skrywer en digter Antjie Krog, skryf in Afrikaans, haar moedertaal, vertaal ander se werk (Nederlands en Vlaams) in Afrikaans, en vertaal haar eie werk (saam met ander vertalers) in Engels. As tweetalige en veeltalige skrywer werk Krog voortdurend op ’n dialogiese en heteroglossiese vlak binne ’n komplekse sosiokulturele en sosiolinguistiese omgewing. Met die skep van tekste wat twee- of veelstemmig is, stel Krog veranderende betekenisse en ontvanklikheid vir verskillende perspektiewe aan die leser bekend – ’n proses wat dikwels haarself, haar taal en ander se taal ontheem of vervreem. Hierdie artikel ondersoek die abjekte soos dit in Krog se teenwoordigheid as selfvertaler en vertaalde skrywer in die Suid-Afrikaanse literêre veld manifesteer. Die abjekte – dit wat onvanpas en vuil is en die geordende sisteem bedreig – is die duidelikste teenwoordig in ons (as subjektiewe persone) reaksies op die fisiese liggaam en die moontlikhede van kontaminasie wat dit inhou. Die skryfproses en die inhoud daarvan, kan en behoort op soortgelyke wyse as ontwrigtende handelinge te funksioneer. Die konsep van die materialiteit van die teks is spesifiek relevant tot Krog se eie poësie, wat ’n abjekte, beliggaamde landskap voorstel. As skrywer bewoon (inhabit) Krog die teks – sy wórd die ritmes en artikulasies van die teks. Binne kulturele vertaling, vorm abjeksie en die mineuraanwending van taal ’n integrale deel van die konstruksie van identiteit en subjektiwiteit. Hierdie abjeksie funksioneer op twee vlakke: aan die een kant is Krog se teenwoordigheid binne die Engelse literêre veld ambivalent, onstabiel en uitdagend van ’n skoon, geordende sisteem; aan die ander kant ondermyn sy die majeurtaal deur haarself met subversiwiteit te vertaal. Die doel van die artikel is om die konsepte abjeksie en mineurtaal te versoen in ’n poging om ’n vars perspektief te gee op die persepsie en resepsie van Krog se werk in die Suid-Afrikaanse literêre veld.  Translation and/as abjection: Antjie KrogExtended abstractInternationally acclaimed South African author and poet Antjie Krog writes in Afrikaans, her mother tongue, translates others’ work (Dutch and Flemish) into Afrikaans, and together with other translators, translates her own work into English. As bilingual or multilingual writer in a complex sociocultural and sociolinguistic environment, Krog continually operates at a dialogic and heteroglossic level. In producing texts that are double-voiced or multi-voiced, she introduces differing meanings and openness to different perspectives, often defamiliarising herself, her own and others’ language, and the reader. This paper seeks to address the notion of the abject as manifest in Krog’s presence as self-translator as well as in her presence as translated writer in the South African literary field. The abject – that which is improper, unclean, threatening the orderly system – is most prevalent in our (subjective beings’) reactions to the physical form of the body and its contaminative possibilities. In a similar vein, writing and its contents, could, and does, function as destabilising acts. The notion of the materiality of the text is particularly relevant to Krog’s own poetry, as her work exhibits an abject, embodied landscape. As writer, Krog inhabits the text and becomes the rhythms and articulations of the text.“God, Death, Love, Loneliness, Man / are important Themes in Literature / menstruation, childbirth, menopause, puberty / marriage are not,” Krog writes in Body bereft (BB 20), highlighting, to a large extent, what Mansfield calls “fantasies of an autonomous selfhood” (Kristeva in Mansfield 2000:82):  “... we draw an imaginary line around the perimeters of our bodies and define our subjectivity as the unique density of matter contained within that line.” This dilemma experienced by the subject could have an additional dimension, namely, “In our fantasy of an autonomous literature or autonomous language […] we draw an imaginary line around the perimeters of our literature and define our literature/language as the unique density of matter contained within that line.” The latter interpretation of Kristeva links to Deleuze and Guattari’s work on minor literature, specifically the hidden potential of a minor use of a major language. Krog’s poem also echoes Christiane Rochefort’s description of the struggle in terms of freedom of the (French) women writer:  “You are supposed, too,” she writes (Rochefort in Jones 1997:380), “to write about certain things: house, children, love. […] Maybe you don’t want to write about, but to write, period. And of course, you don’t want to obey this social order. So, you tend to react against it” (italics in original).  Krog’s oeuvre in the Afrikaans and English literary field in South Africa consists of Afrikaans poetry volumes, prose, prose translations from English and Dutch, and translations of her own and others’ poetry. Her first non-fiction book is published in 1995 (Relaas van ’n moord; Account of a murder, 1997), followed by her first publication in English in 1998, Country of my skull. Thereafter followed the autobiographical/fictional work A change of tongue (2003; published in 2005 as ’n Ander tongval), her most recent non-fiction book being Begging to be black (2009). With Country of my skull and A change of tongue Krog acquired international status, but mostly made the transition to bilingual or multilingual writer occupying the interesting yet ambivalent space of hybridity, heterotopias and the cosmopolitan. In 1995 she started working as translator of Nelson Mandela’s autobiography into Afrikaans, followed by various translations and anthologies; the most recent being her second anthology in English translation, Skinned (2013).It is argued that in translating her own work from Afrikaans, a minoritised language post-1994, into a language of power, English, Krog abjectifies the major language, thereby creating a delicate space in the target cultural field: a space where the language is double, vague, heterogeneous, metamorphosed, deterritorialised, reterritorialised; a space where her translations open up “revolutionary conditions […] within the heart of what is called great (or established) literature” (Deleuze & Guattari 1986:18). Entering the Afrikaans literary field at a stage where it was a major (institutionalised) literature in South Africa, Krog’s style was less conventional and her subject matter daring. With Country of my skull, A change of tongue and Down to my last skin, Krog moved from minor (Afrikaans) to major language, utilising a type of English (South African, with heavy Afrikaans undertones) that constitutes a minor use of the major language (see Pakendorf 1993). In Krog’s approach to retain the Afrikaans undertones she manages to keep alive the contact zone between Afrikaans and English as a space of multiple articulations where language need not function as a defining or limiting border. It is perhaps safe to position Krog in a hybrid space within the English literary field. This in-between space, or third space, presents itself as uncomfortable and revealing, and as symptomatic of the tension between two more defined spaces from the English reader’s perspective: the one known, global, intimidating, levelling (English), the other unknown or foreign (Afrikaans), yet local.In Deleuze and Guattari’s framework, innovation or novelty in language usage is what opposes the attraction of a higher, dominant order, creating a new literary continent or space that is neither conformist nor idealistic. On the level of the abject, Krog creates such a space in Country of my skull and A change of tongue, and again in Verweerskrif and Body bereft, paving the way for the conceptualization of an international and cosmopolitan culture based on the inscription and articulation of cultural hybridity. Moreover, she views translation as the transformation of one text from a powerless language into a powerful one; the transformation of a powerful text that was made powerless by a powerless language, becoming empowered in and through the powerful language (Krog 2002b:2).As forms of textual and cultural translation, abjection and minoritisation form an integral part in the construction of identity and subjectivity. This abjection is operative on two levels: on the one hand Krog’s presence in the English literary field is ambivalent, unstable and daring to a clean, orderly system; on the other hand she undermines the major language by translating herself and her non-orderly self with subversion. The aim of this paper is to merge the concepts of minoritisation and abjection in an attempt to bring a fresh perspective on the perception and reception of Krog’s work in the South African literary field.